On Time Performance pada Bandara Internasional Soekarno-Hatta - Siahaan, Julyanthi Marine; Ricardianto, Prasadja; Kurniawan, Jermanto Setia; Setiawan, Edhie Budi; Abidin, Zaenal (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The research objective is to determine the direct contribution and indirect effect of airport officers’ competence and performance on On Time Performance mediated by delay management supervision in Soekarno-Hatta International Airport. The importance of the Air Transport Inspector performance in supervising is required to improve the performance of the employees. The method used in this study was a Descriptive Quantitative using survey. The population were all flight service inspectors. The study used Smart Partial Least Square path analysis method with purposive sampling of 72 respondents. The results of the analysis show that there are three direct contributions which are officers’ competence on Delay Management supervision, officers’ performance on DelayM anagement supervision and Delay Management supervision on OTP. Delay Management supervision is able to mediate the competence and performance on On Time Performance in Soekarno-Hatta International Airport.